Herpes Simplex Virus Type 1 Engages Toll Like Receptor 2 to Recruit Macrophages During Infection of Enteric Neurons - Brun, Paola; Scarpa, Melania; Marchiori, Chiara; Conti, Jessica; Kotsafti, Andromachi; Porzionato, Andrea; De Caro, Raffaele; Scarpa, Marco; Calistri, Arianna; Castagliuolo, Ignazio (Frontiers in Microbiology, 2018)
Herpes simplex virus type 1 (HSV-1) is a widespread neurotropic pathogen responsible for a range of clinical manifestations. Inflammatory cell infiltrate is a common feature of HSV-1 infections and has been implicated in neurodegeneration. Therefore, viral recognition by innate immune receptors (i.e. TLR2) and the subsequent inflammatory response are now deemed key players in HSV-1 pathogenesis. In this study we infected with HSV-1 the enteric nervous system (ENS) of wild-type (WT) and TLR2 knock-out (TLR2ko) mice to investigate whether and how TLR2 participates in HSV-1 induced neuromuscular dysfunction. Our findings demonstrated viral specific transcripts suggestive of abortive replication in the ENS of both WT and TLR2ko mice. Moreover, HSV-1 triggered TLR2-MyD88 depend signalling in myenteric neurons and induced structural and functional alterations of the ENS. Gastrointestinal dysmotility was however less pronounced in TLR2ko as compared with WT mice. Interesting, HSV-1 caused up-regulation of monocyte chemoattractant protein-1 (CCL2) and recruitment of CD11b+ macrophages in the myenteric ganglia of WT but not TLR2ko mice. At the opposite, the myenteric plexuses of TLR2ko mice were surrounded by a dense infiltration of HSV-1 reactive CD3+CD8+INFγ+ lymphocytes which accounts for the described gastrointestinal dysmotility. Indeed, depletion CD3+CD8+ cells by means of administration of anti-CD8 monoclonal antibody reduced neuromuscular dysfunction in TLR2ko mice infected with HSV-1. During HSV-1 infection, the engagement of TLR2 mediates production of CCL2 in infected neurons and coordinates macrophage recruitment. Bearing in mind these observations, blockage of TLR2 signalling could provide novel therapeutic strategies to support protective and specific T-cell responses and to improve neuromuscular dysfunction in pathogen-mediated alterations of the ENS.